The relevance of library and information services for the visually impaired in Nigeira (2007)
The paper discusses the relevance of library and information services to the visually impaired persons in Nigeria. The visually impaired persons have some peculiarities and their disabilities vary according to the degree of severity requiring tailored library and information services, which is responsive to individuals needs. It acknowledges government efforts as well as that of organizations and individuals in the educational provisions for the visually impaired in the country since 1957, though library and information services are still in thier infancy. Problems encountered by the visually impaired in an attempt to have access to library services are also highlighted while recommendations were proffered for developing library and information services for this category of handicapped people.